Polyp size and sex of Dendrophyllia ramea specimens from the Alboran Sea, Western Mediterranean - Orejas, Covadonga; Antón-Sempere, Silvia; Terrón-Singler, Alexis; Grau, Amalia (In: Orejas, C et al. (2023): Reproductive features and gametogenesis of Dendrophyllia ramea from the Alboran Sea, Western Mediterranean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.957212, 2023)
This data set contains information on polyp size and sex: biometric data of polyps from Dendrophyllia ramea, as well as the sex of each analysed polyp. A total of three polyps have been analysed per each coral colony and a total of three coral colonies have been analysed for each sampling month: February 2018, May 2017, July 2018 and October 2017. Samples have been collected in the protected area of Punta La Mona (Granada, Alborán Sea, western Mediterranean) between 30 and 37 meters depth by scuba diving.
Keywords: Alboran Sea; cold-water corals; Dendrophyllia ramea; gametogenesis; Reproduction; Western Mediterranean Sea